(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Family planning (FP) integration in other services is essential to address unmet FP needs among postpartum women and reduce the risks of short pregnancy intervals. Immediate postpartum family planning (PPFP) is an established high-impact practice. This study aimed to assess the uptake of immediate PPFP utilization before and after implementation in various project interventions. Methods: Capacity building of 276 health care providers was conducted in 100 facilities by 32 established FP mentors through facility-based mentorship, emphasizing quality counseling. PPIUCD sets were procured and distributed to 80 facilities. 165 health care workers were oriented on facility consumption data reports and requests (FCDRR) to improve commodity availability. Monthly FP dashboard meetings were held at the subcounty level. FP registers were availed in postnatal wards, and messaging and FP referrals were performed by community health volunteers. For voluntarism, FP compliance sessions were conducted with service providers, and PPFP quality improvement approaches were implemented in eight facilities. Results: 927 and 542 women received immediate PPFP in Homa Bay and Vihiga Counties, respectively, accounting for 11% and 17% of women who delivered in the facilities. The proportion of women who delivered in the facilities received PPFP within 48 hours changed one year later, with 397 women or 3.8% of deliveries between October and December 2021. Health facility baseline assessment demonstrated gaps in the uptake of contraceptives in the immediate postpartum period, including inadequate counseling during antenatal care, lack of postpartum intrauterine device (IUD) insertion skills, lack of PPIUD kits, and lack of commodities and of reporting tools. Conclusion: The untapped demand for immediate PPFP can be met through targeted interventions to improve access and quality of the service.